Uji Toksisitas Akut Ekstrak Etanol Daun Sapu Jagad (Isotoma longiflora (L) Presl.) pada Mencit Galur Mus muculus - Ira Safitri; Inayah Inayah (Jurnal Ilmu Kedokteran, 2010)
Sapu Jagad (Isotoma longiflora (L) Presl.) plant has been empirically used as traditional medicine. Some studies showthat this plant has pharmacological effects as antibiotic, anticancer, and analgetic. It is of importance to conduct studyin finding out the safetiness of this plant as herbal medicine. Therefore, we conducted study to find out lethal dose ofits leaves on mice (Mus muculus) using acute toxicity test. Several doses have been given to certain groups to find outits effect including death. The extract has been given one time per oral. Then, we recorded the clinical signs and deathof mice until 14 days. The data was analyzed using probit analysis to measure LD50. This study shows that ethanolextract of Sapu Jagad leaves has LD50 12.610 mg/kgBW and toxicity of central nervous system proven by seizureending with death. As conclusion, this extract has toxicity especially to central nervous system.